Movement Disorders Associated with Hypogonadism. Issue 7 (29th July 2021) - Gonzalez‐Latapi, Paulina; Sousa, Mario; Lang, Anthony E.
ABSTRACT: A variety of movement disorders can be associated with hypogonadism. Identification of this association may aid in guiding workup and reaching an accurate diagnosis. We conducted a comprehensive and structured search to identify the most common movement disorders associated with hypogonadism. Only Case Reports and Case Series articles were included. Ataxia was the most common movement disorder associated with hypogonadism, including entities such as Gordon‐Holmes syndrome, Boucher‐Neuhäuser, Marinesco‐Sjögren and Perrault syndrome. Tremor was also commonly described, particularly with aneuploidies such as Klinefelter syndrome and Jacob's syndrome. Other rare conditions including mitochondrial disorders and Woodhouse‐Sakati syndrome are associated with dystonia and parkinsonism and either hypo or hypergonadotropic hypogonadism. We also highlight those entities where a combination of movement disorders is present. Hypogonadism may be more commonly associated with movement disorders than previously appreciated. It is important for the clinician to be aware of this association, as well as accompanying symptoms in order to reach a precise diagnosis.